From ad hoc to strategic ecosystem management: the "Three‐Layer Ecosystem Strategy Model" (TeLESM). Issue 7 (19th April 2017) - Holmström Olsson, Helena; Bosch, Jan
Abstract: Recently, business ecosystems have been recognized as one of the most interesting phenomenon in software engineering research. Companies experience a paradigm shift where product development and innovation is moving outside the boundaries of the firm and where networks of stakeholders join forces to co‐create value. While there is prominent research focusing on the managerial perspective of business ecosystems, few studies provide strategic guidance for how to intentionally manage the different ecosystems that companies operate in. Therefore, and on the basis of multicase study research, we provide empirical evidence on the challenges that software‐intensive companies experience in relation to the different types of business ecosystems they operate in. We conduct a "state‐of‐the‐art" literature review to identify strategies that are used to manage ecosystem engagements, and we develop a conceptual model in which we identify strategies for managing the innovation ecosystem, the differentiating ecosystem, and the commoditizing ecosystem. By categorising the different strategies in relation to the different types of ecosystems for which they are valid, the "three‐layer ecosystem strategy model" provides comprehensive support for strategy selection. We validate the use of the identified strategies in 6 software‐intensive case companies, and we provide empirical insights on the "relevance" and the "desired use" of these strategies as experienced by the case companies. Abstract : This work provides empirical evidence on the challenges that software‐intensive companies experience in relation to ecosystem management. We conduct a literature review where we identify strategies to manage these challenges, and we develop the "three‐layer ecosystem strategy model." The model identifies strategies for managing the innovation, the differentiating, and the commoditizing ecosystem. We validate the use of the strategies, and we provide empirical evidence for the "relevance" and the "desired use" of these as experienced by the case companies.